Differential responsiveness of distinct retinal domains to Atoh7 - Sinn, Rebecca; Heermann, Stephan; Wittbrodt, Joachim (Mechanisms of development, 2014)
During vertebrate eye development retinal progenitor cells (RPCs) differentiate into all neural cell types of the retina. Retinal ganglion cells (RGCs) represent the first cell type to be generated. For their development, Atoh7, a basic Helix Loop Helix (bHLH) transcription factor is crucial. Atoh7 loss of function results in a massive reduction or even a total loss of RGCs. However, inconsistent results have been obtained in atoh7 gain of function experiments with respect to ganglion cell genesis, implying that the effect of Atoh7 is likely to be dependent on the competence state of the RPC. In this study we addressed the differential susceptibilities of early RPCs to Atoh7 in vivo, using medaka. Unexpectedly, we observed a largely normal development of the dorsal retina, although atoh7 was precociously expressed. However, the development of the retina close to the optic nerve head (part of the ventral retina) was disturbed severely. Photoreceptors were largely absent and the Müller glia cell number was reduced significantly. The majority of cells in this domain were ganglion cells and the abnormal development of this area affected the closure of the optic fissure resulting in coloboma.
Gesehen am 08.02.2017